Pengaruh Variasi Pencil Lead Electrode (PLE) terhadap Deteksi Ion Logam Pb (II) menggunakan Modifikasi MnO2 Metode Voltametri Siklik - Wahyuni, Rahmi; Sari, Trisna Kumala (MASALIQ, 2025)
This study is motivated by the limited research on modified pencil lead electrodes in electrochemical detection, despite their significant potential as simple, low-cost, and environmentally friendly heavy metal sensors. The aim of this research is to evaluate the performance of MnO₂/pencil lead electrode (MnO₂/PLE) with variations in pencil hardness—2B, B, and HB—in detecting K₃[Fe(CN)₆] and Pb²⁺ ions using cyclic voltammetry. The electrodes were modified using the drop-casting method, and voltammogram data were analyzed based on current and redox potential values. The results show that MnO₂/PLE (2B) demonstrated the best performance among the variants. This is attributed to the synergy between the electrocatalytic properties of MnO₂ and the high graphite content of the 2B pencil, which enhances conductivity and electrochemical response. MnO₂/PLE (2B) proved effective in detecting Pb²⁺ ions, making it a strong candidate for use as an electrochemical heavy metal sensor. The implications of this study contribute to the literature on modified carbon-based sensors and open opportunities for the development of portable, low-cost sensors for environmental monitoring.